Voter turnout in Portugal: a geographical perspective - Manoel, Liliana Alexandra Silvério Raposo Guerreiro da Câmara (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management